Effects of Internal Pressure on Urban Water Supply Pipeline Leakage-Induced Soil Subsidence Mechanisms - Cui, Jingyu; Liu, Fengyin; Chen, Ruidi; Wang, Shuangshuang; Pu, Cheng; Zhao, Xu (Geofluids, 2024)
After the rupture of pressurized water supply pipes in urban underground areas, seepage-induced ground subsidence becomes a severe geological hazard. Understanding the permeation and diffusion patterns of water in soil is crucial for deciphering the mechanisms underlying soil settlement and damage. Notably, the pressure within water supply pipes significantly influences the settlement and damage of the soil. Therefore, this study simulated experiments on soil settlement and damage caused by water seepage from a preexisting damaged pipeline under various internal pipe pressure conditions using an indoor model apparatus. The results indicate that the internal pressure of the pipe significantly influences the settlement of the soil. High-pressure seepage causes noticeable erosion in the soil, forming cavities within it. In contrast, low-pressure seepage results in water diffusing in an ellipsoidal pattern, leading to the formation of circular surface cracks. The degree of surface settlement increases with higher pipe pressure. The onset of subsidence at a specific point on the ground is not directly related to whether the moistening front within the soil has reached that point horizontally. Instead, it is associated with the moisture content below the subsidence point within the soil. The research results further illustrate the water diffusion and moisture content increase processes after water seepage from pipes with different pressures, revealing the influence of pipe pressure on the degree and form of soil settlement damage and clarifying the relationship between water diffusion and settlement in the soil.